2021
DOI: 10.1186/s40478-021-01151-4
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of mesenchymal transformation in glioblastoma

Abstract: Despite aggressive multimodal treatment, glioblastoma (GBM), a grade IV primary brain tumor, still portends a poor prognosis with a median overall survival of 12–16 months. The complexity of GBM treatment mainly lies in the inter- and intra-tumoral heterogeneity, which largely contributes to the treatment-refractory and recurrent nature of GBM. By paving the road towards the development of personalized medicine for GBM patients, the cancer genome atlas classification scheme of GBM into distinct transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 186 publications
(215 reference statements)
7
84
0
Order By: Relevance
“…We showed that the proneural-to-mesenchymal transition is independent of histological feature composition and reflects transcriptional changes in the cellular tumor. Mesenchymal transitions have been shown to associate with several factors, including increased myeloid cell infiltration, radiation-induced NF-κB activation, altered tumor metabolism, and hypoxia (Bhat et al, 2013;Garofano et al, 2021;Kim et al, 2021;Mao et al, 2013;Osuka et al, 2021;Schmitt et al, 2021;Wang et al, 2017). Our results indicate that the proneural-tomesenchymal transition is likely influenced by tumor-wide changes, supporting the hypothesis that this transition is involved in therapy resistance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We showed that the proneural-to-mesenchymal transition is independent of histological feature composition and reflects transcriptional changes in the cellular tumor. Mesenchymal transitions have been shown to associate with several factors, including increased myeloid cell infiltration, radiation-induced NF-κB activation, altered tumor metabolism, and hypoxia (Bhat et al, 2013;Garofano et al, 2021;Kim et al, 2021;Mao et al, 2013;Osuka et al, 2021;Schmitt et al, 2021;Wang et al, 2017). Our results indicate that the proneural-tomesenchymal transition is likely influenced by tumor-wide changes, supporting the hypothesis that this transition is involved in therapy resistance.…”
Section: Discussionsupporting
confidence: 77%
“…The mesenchymal subtype of glioma is associated with increased accumulation of immune cells, primarily of the myeloid lineage (Bhat et al, 2013;Kim et al, 2021;Wang et al, 2017). We thus hypothesized that interactions between the tumor-infiltrating myeloid cells and malignant cells can influence the tumor's trajectory at recurrence.…”
Section: Mesenchymal Tumor Cell Activity Associates With a Distinct Myeloid Cell Phenotypementioning
confidence: 99%
“…Mesenchymal transformation is a hallmark of tumor heterogeneity that has been associated with a more aggressive phenotype and therapeutic resistance 13,15,18 . Mesenchymal transformation involves fibroblast-like morphological changes associated with active migration and gain of expression of mesenchymal genes as previously described 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrating morphological features, spatially resolved transcriptomics, and cellular dynamics resulting from mesenchymal transformation, growth, and invasion are thus of great relevance to our understanding of glioma progression 13,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic, methylation, mutational and mesenchymal signatures following radiotherapy all have been reported to correlate with patient's prognosis in glioblastoma (GBM) (168)(169)(170)(171)(172). For example, gene signatures focusing on mesenchymal traits, which can be induced by radiation, distinctively correlate with worse prognosis (173). Within this present study, upregulation of the Epithelia Mesenchymal Transition gene set was only correlated with a worse prognosis in CESC patients, highlighting the importance of distinct approaches for each tumor type, and even tumor subtype.…”
Section: Discussionmentioning
confidence: 99%